A Caracterização do diploma de graduação digital por meio da diplomática contemporânea - CRUZ, Fernanda Di Paula Sousa da (2022)
Since the beginning of the 17th century, Diplomatic has had the purpose of assisting in the authenticity of documents. With technological advances and the emergence of new Information and Communication Technologies (TIC), there was a need to adapt Diplomatic in order to meet the new reality of naturally digital documents. In order to optimize time and reduce bureaucracy in some administrative activities of Higher Education Institutions (IES), the Ministry of Education (MEC) launched the digital undergraduate diploma through ordinance Nº 554 of March 11, 2019, highlighting the need to characterize the digital diploma. The general objective is to analyze and identify the elements of the digital diploma structure that will guarantee its authenticity and veracity, the specific objectives being to present the historical-conceptual course of diplomatic, to identify the elements that make up the structure of the physical and digital diploma based on ordinances Nº 1095 of October 25, 2018 and Nº 554 of March 2019, respectively, to demonstrate the aspects and propose to the characterization of the digital diploma using the model of the Federal University of Pará. The methodology was qualitative, descriptive and exploratory, through data collection on the Digital Diplomatic theme, digital document and physical document, in addition to a study applied to ordinances dealing with the issuance and registration of physical and digital diplomas. The research showed that all the mandatory elements present in the physical diploma remained in the digital, the difference is in the way the data is presented, since, in the digital diploma, the data are in XML language with the XSD schema. Finally, there was a need to develop a model of diplomatic analysis for naturally digital documents, as well as the need for scientific production on the topic of Digital Diplomatics.